Contribution Of Students in Guidance and Counseling Study Program While Doing Real Work College Services In Bungursari Village - Anugerah, Dandi; Yahya, Muhammad Ilham; Annur M, Ade Isna; H, Yunita Sri; Nizar P, Ajeng; Novitasari, Aliffiah; Nurazizah, Dina; Anggita, Sahira; Salsabila, Nabila; Rizal, Fahrul; Maruf, Cipta Muhammad; Alysa F, Ayunda; Nurul Istiqomah, Insya Siti; Nuryuniarti, Rissa (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The current phenomenon is the lack of children's insight into the ideals of modern times which should be easy to obtain information. This activity must be done so that children can plan their future better. The team carried out several methods starting from finding out how far the children knew their ideals, then continued by explaining their goals to the children, then watching the children's development about the knowledge of their goals, after that the team reaffirmed the goals of each child, and the latter create from cardboard tree and hang on to the ideals they have written down. As a result, the children understand more about what the team has explained about their goals and it turns out that they can understand and understand more than before. There are children who initially have an unnatural aspiration to become a reasonable profession. From the results of the needs analysis carried out in 3 stages, namely PAUD, MI, SMA Find problems in early childhood, children lack knowledge about emotions. So we made a motivational poster to provide children with early childhood knowledge through the media and visualized it with pictures, we found problems in this, lack of knowledge about the future related to high school goals, lack of interest and talent to continue higher education due to lack of direction in the future.